Nurses' Knowledge, Attitude, and Work Fatigue with Needle Sticks - Alya Ismi Mustapa; Ihya Hazairin Noor; Anggun Wulandari; Mufatihatul Aziza Nisa; Agung Waskito (Lambung Mangkurat University, 2023)
Needlestick incidents are caused by hypodermic syringes, blood draw needles, and connecting needles from intravenous delivery systems which can accidentally puncture the skin, causing injury. WHO states that NSI include to one of the top serious occupational hazards among health workers, including nurses, with >2 million incidents among 35 million health workers. In Indonesia, there was a cohort study which resulted in the finding of 286 cases of NSI with the most frequent occurrence in nurses (42.7%) with an incidence rate of 15.2 out of 1,000 people per year. The purpose of this research is to determine the relationship between knowledge, attitudes, work fatigue of NSI among nurses at Hospital X. This research uses a quantitative cross sectional design. The population was 275 nurses with 80 sample size. This research instrument used a questionnaire. The Fisher Exact test show the result of the research which there is a significant relationship between knowledge and attitudes towards the incidence NSI in nurses (p-value 0.003 and 0.013), while the work fatigue variable does not have a significant relationship with the incidence of NSI (p-value 1.000). It is hoped that the K3 Program can be implemented as an effort to prevent NSI in nurses.